KAJIAN IDENTIFIKASI KETERSEDIAAN BAHAN ORGANIK DI BEBERAPA TIPE PENGGUNAAN LAHAN SAWAH - Sofyan, Adnan; Abadan, Afyanto; Umasugi, Buhari; Ali Hasan, Asrul Dedy; Abd Rachman, Idris (Jurnal Pertanian Khairun, 2025)
Organic materials refer to substances derived from plant or animal waste and by-products, including manure, composted rice straw, plant residues, sewage, green manure, legume cuttings, and municipal or industrial waste (Zaini et al., 2004, cited in Pirngadi, 2008). This study aims to assess the level of organic material availability and identify the factors influencing it. The parameters analyzed include soil pH, total nitrogen (Total-N), organic carbon (C-organic), organic materials, water content, and the C/N ratio. The research was conducted in Subaim, Bumi Restu Village, in the Wasile District of East Halmahera Regency.The calculation of organic material values involved multiplying the C-organic content by a factor of 1.74%. The findings reveal that the average organic material content across various types of rice field land uses ranges from moderate to high, specifically between 4.12% and 4.43%. The higher levels of organic materials are attributed to the application of rice straw and organic fertilizers during post-harvest and land preparation phases. Conversely, lower organic material values are primarily due to the significant consumption of organic matter by plants during their growth stages